ASEAN De-dollarization Strategy to Reduce Dependence on the US Dollar - Bustami, Sirwan Yazid; Ramdiana, Laili Rohmi (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This research aims to analyze the ASEAN de-dollarization strategy to reduce dependence on the use of the US dollar in international transactions in Southeast Asia. It uses a qualitative approach with an analytical descriptive method. Data was collected through literature review and analyzed through several stages, namely data reduction, data presentation, and conclusion. Data reduction is done by reviewing the collected data to be selected according to research topic. Furthermore, data presentation stage was carried out in form of a narrative. Finally, conclusion is drawn based on elaboration of theory of regulatory regionalism and regional monetary cooperation. Based on research results, the ASEAN de-dollarization strategy is implemented through several forms, namely regional payment system, regional liquidity sharing, regional exchange rate coordination, and regional financial market development. The regional payment system is implemented by establishing regional payment connectivity and local currency transaction mechanisms. On other hand, regional liquidity sharing is carried out by enforcing foreign exchange swap mechanism. Meanwhile, regional exchange rate coordination is done by establishing ASEAN+3 Macroeconomic Research Office, enforcing external balance assessment mechanism, and establishing ASEAN+3 Currency Swap Arrangement mechanism. Finally, development of regional financial markets will be achieved through establishment of ASEAN Capital Market Forum, ASEAN Banking Integration Framework, ASEAN+3 Bond Market Forum, and ASEAN Infrastructure Fund. These strategies are proven to have an impact on reducing dependence on the US dollar